Frequency and perception of buffalo meat consumption by the population of Belem do Pará, Brazil - Pamella M. M. de Jesus; Mayrla F. Dantas; Luiz H. M. Martins; Antônio V. C. Barbosa; Natalia G. S. Barbosa (Revista Científica)
Belem City is characterized by its diversity in products of animal and vegetable origin. Currently, it is the second most populous city in the northern region. This large population increases the demand for foodstuffs. The objective of this study was to evaluate the profile, preference, habit, and frequency of consumption of beef, buffalo, chicken, fish, and swine meat in Belem - PA. Data collection was carried out in 2019. The sample was composed of 400 interviewees chosen randomly from various points of sale in the city, such as fairs, butchers, and supermarkets, among others. It was found that 51.9% of the consumers were women and 48.1% were men aged between 15 and 29 years; the family environment was composed of three to four people, and 41.6% had income between a minimum wage; 51.9% had completed high school. It was observed that the consumers of Belem preferred beef (51%), followed by these meats: chicken (33%), fish (10%), buffalo (5%) and swine (1%). 64.2% of the frequency of consumption of beef and buffalo was between one and two kilograms per week, while for chicken, fish, and pork, this frequency was 72.4% for the same volume of meat. 70.2% of the respondents had the habit of consuming beef two to three times per week, while 62.7% consumed chicken, fish, and swine at least two to three times a week. Only 7.3% said that they consume buffalo meat once a week. Knowledge about the benefits of buffalo meat was considered low. 70.7% of the sample did not know how to comment about it. 22.8% of the interviewed bought primary beef and buffalo cuts and 53.1% chicken drumsticks. These meats were bought mainly from butchers (48.1%). According to 80.2% of interviewees, chicken is the product that replaces beef and buffalo.